ANALYSIS OF REQUIREMENTS FOR CHILDREN'S CLOTHES - R. A. Ergasheva; DH Rayimberdiyeva (American Journals, 2022)
In the article, marketing research was conducted in local markets of Namangan region and district for the production of a set of girls' clothes, and consumer demand was studied. Based on the results of the research, it was analyzed that there is a high demand for national adras fabric models sewn for children's clothes with simplicity, various kant, core stitches, zippers.